Penerapan Model Agile dan Extreme Programming Dalam Merancang Aplikasi E-Learning dengan Bahasa Dart-Flutter Berbasis Android (Kasus TK Nurul Hikmah) - Susi Widayati; Yudi Irawan Chandra; Ferlita Anjani (LPPM STIKOM Tunas Bangsa, 2023)
Character education in early childhood is very important, because early childhood is able to capture quickly what they see and imitate it, but with the Covid-19 pandemic all activities must be carried out online. One of them is Nurul Hikmah Kindergarten which conducts online learning, but with limited knowledge about the use of technology in the area, the teachers do not know how to handle it, therefore this research aims to help Nurul Hikmah Kindergarten in Distance Learning (Online) and introduce technology to teachers and parents of Nurul Hikmah Kindergarten students. Nurul Hikmah Kindergarten was chosen because this school was affected by the covid-19 pandemic and limited teacher knowledge about online learning. The research method used is the Agile Method which is one type of method in software development. Usually often referred to as SDLC (Software Development Life Cycle). Startups and large companies often use this method in software development. The Extreme Programming model (hereafter abbreviated as XP) is used because it has the advantage of simplifying the various stages in the development process to be more adaptive and flexible. XP does not only focus on coding but covers all areas of software development, and XP takes an 'extreme' approach to iterative development. Application development is done using Flutter / Dart programming language. The result of this research is the Pena Application can run well on Android mobile devices; besides that, it can provide solutions to problems that exist in Nurul Hikmah Kindergarten